15m+6.3=9.8

Simple and best practice solution for 15m+6.3=9.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15m+6.3=9.8 equation:


Simplifying
15m + 6.3 = 9.8

Reorder the terms:
6.3 + 15m = 9.8

Solving
6.3 + 15m = 9.8

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6.3' to each side of the equation.
6.3 + -6.3 + 15m = 9.8 + -6.3

Combine like terms: 6.3 + -6.3 = 0.0
0.0 + 15m = 9.8 + -6.3
15m = 9.8 + -6.3

Combine like terms: 9.8 + -6.3 = 3.5
15m = 3.5

Divide each side by '15'.
m = 0.2333333333

Simplifying
m = 0.2333333333

See similar equations:

| abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 | | B-(2)=-11 | | 14-4y=y+x | | 1n+3-1=8 | | y-34=41/11(20-6) | | 3x-24=2x+26 | | y-34=41/11(18-6) | | 14x^2+9x=-1 | | -4+6(x-4)=15x+2-9x | | y-4/3-7=.25 | | 6n+3(n+2)=-(2n+7)+n | | -6m=42 | | 5x(2x+7)=2 | | 14x-8=34 | | 6-y/(-1)=0 | | 11-(3v+5)=3v-6 | | .15x=23 | | 3w+6-w=5w-2(w-3) | | 7y-4=216-2x | | 15-3.2x=-6.8 | | 8x+15=-57 | | (m+1.5)=1.5(2m+3) | | y=-x^2+8x-19 | | x+6(x-50)=750 | | 3y+2(y-5)=-1(3y-35)-y | | .55+q=.66 | | 5x-(2x+7)=2 | | -2(n+2)+6=16 |

Equations solver categories